2016
DOI: 10.1007/s10098-016-1145-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of including land-use change emissions from biofuels on meeting GHG emissions reduction targets: the example of Ireland

Abstract: The greenhouse gases (GHG) emissions from land-use change are of particular concern for land-based biofuels. Emissions avoided by substituting fossil fuels with biofuels may be offset by emissions from direct and indirect land-use changes (LUC). There is an urgent need to investigate what impact land-use change emissions may have on the expansion of bioenergy and biofuels, in the context of EU mitigation policies. This paper focuses on Ireland, which faces a number of challenges in delivering its renewable ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These studies analyze the inclusion of new technologies or energy sources in the economy without focusing on one single sector. For example, Czyrnek‐Delêtre et al () focus on the effects of indirect land use on the expansion of biomass and bioenergy used in the industry, transport and electricity, in the context of mitigation policies. Other authors, such as Sgobbi et al () study the introduction of alternative sources of energy such as hydrogen, in the energy matrix, again, without particular interest in one or another sector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies analyze the inclusion of new technologies or energy sources in the economy without focusing on one single sector. For example, Czyrnek‐Delêtre et al () focus on the effects of indirect land use on the expansion of biomass and bioenergy used in the industry, transport and electricity, in the context of mitigation policies. Other authors, such as Sgobbi et al () study the introduction of alternative sources of energy such as hydrogen, in the energy matrix, again, without particular interest in one or another sector.…”
Section: Resultsmentioning
confidence: 99%
“…As pointed out by Krey (2014), the system boundaries of models are being extended to address the interlinkages between human, technical, and natural systems more comprehensively. Other environmental interests are air pollution (Pan, Xie, & Li, 2013;Proost et al, 2000;Rafaj & Kypreos, 2007), water demand (Agrawal, Ahiduzzaman, & Kumar, 2018;Bouckaert et al, 2012;Huang, Ma, & Chen, 2017) and land use (Czyrnek-Delêtre et al, 2016). Research opportunities can be found even within the already saturated climate change mitigation scope.…”
Section: Background Informationmentioning
confidence: 99%
“…This can be done when choices are made with respect to system boundaries (e.g., TH, allocation assumptions, carbon stock changes). This single bioenergy EF can be used in energy system models just like conventional hydrocarbon fuels (as done in Czyrnek-Delêtre et al, 2016). However, by including those (static) EFs, the temporal dynamic nature of short-and long term LUC emissions is not captured.…”
Section: Dynamic Emissionsmentioning
confidence: 99%
“…Limited studies have investigated the dynamic link between spatially explicit GHG quantification of bioenergy and national energy systems, which is recommended by Köberle (2018) for assessing GHG mitigation strategies. Czyrnek-Delêtre et al (2016) claim to be the first to assess the impact of LUC emissions on the demand for bioenergy in a low-carbon energy system. They show that the total primary bioenergy demand reduces with approximately 70% when LUC emissions are included, compared to a scenario excluding LUC emissions, resulting in radical changes especially in a low-carbon transport sector.…”
Section: Introductionmentioning
confidence: 99%
“…First generation ethanol production: Ethanol is synthesized both, chemically (synthetically) from petrochemicals like petrol or through microbial fermentation from a large number of agricultural carbohydrates and products (Czyrnek-Delêtre et al;Badger, 2002;Brooks, 2008). Bioethanol is a promising biofuel of great alternative prospective to fossil fuels (Adnan et al, 2014).…”
Section: St Generation Biofuels (Biodiesel Bioethanol Pure Plantmentioning
confidence: 99%